Safety behaviors and degradation mechanisms of aged batteries: A review - Shuguo Sun; Jun Xu (Energy Materials and Devices)
As lithium-ion batteries (LIBs) become increasingly widespread, ensuring their safety has become a primary concern. Particularly, battery aging has been reported to significantly impact major battery safety behaviors, including the internal short circuit (ISC) and thermal runaway (TR). Over the past decade, despite considerable research into the thermal hazards of aged batteries, the complexity of battery aging and TR mechanisms, along with the challenges posed by extreme experimental conditions, necessitates a systematic understanding. Aiming to provide a comprehensive review of safety issues related to aged batteries, this paper begins by exploring the fundamental aging mechanisms and factors that accelerate aging. It then investigates how aging affects battery safety issues, including swelling and off-gassing behaviors. Furthermore, we discuss the impact of aging on TR problems induced by abusive conditions, covering safety issues from internal sources to external abusive scenarios. This review offers valuable insights into understanding and predicting the thermal hazards of aged LIBs, which provides guidelines for designing and manufacturing safer LIBs and accurate and rapid battery safety prognostics in the future.